The Impact of Clinical Presentation on Survival in Patients Requiring Hemodialysis Catheters for Acute and Unplanned Dialysis: A Prospective Observational Study. (April 2021) - Talbot, Benjamin; Lin, Ray; Li, Qiang; Jun, Min; Kotwal, Sradha; Sen, Shaundeep; Gallagher, Martin
Background: Most studies addressing hemodialysis initiation with a dialysis catheter focus on patients entering maintenance dialysis programs and exclude other patients, such as those with acute kidney injury (AKI), making interpretation and application of the results difficult for clinicians managing patients at the time of dialysis commencement. Objective: To compare the survival of all patients requiring a catheter for hemodialysis access according to the nature of clinical presentation. Design: Prospective observational. Setting: An Australian tertiary renal unit. Patients: All patients requiring a central venous catheter (CVC) for hemodialysis access between 2005 and 2015. Measurements: Baseline comorbidities, demographics, and nature of clinical presentation. Data regarding each episode of dialysis access insufficiency and each CVC were collected. The primary outcome was all-cause mortality. Methods: Patients were classified into 1 of 3 groups based on physician assessment at the time of presentation: patients believed to have AKI with expected renal recovery (AKI), patients considered to be entering the maintenance dialysis program without a functioning dialysis access (Maintenance Dialysis), patients unable to perform peritoneal dialysis, or use their existing hemodialysis access (Access Failure). Time-split multivariable Cox regression analyses were used to compare survival between groups. Results: A total of 557 eligible patients had complete prospective data regarding CVC use and were included in the analyses. The majority of patients were in the AKI (246/557, 44%) and Maintenance Dialysis groups (182/557, 33%) compared with the Access Failure group (129/557, 23%). During a median follow-up of 3 years, 302 (54%) of the 557 patients died. Following adjustment, risk of all-cause mortality was higher in the AKI group (hazard ratio [HR]: 2.01, 95% confidence interval [CI]: 1.31-3.60, P = .001) during the first 2 years after catheter insertion and lower in years 2 to 4 (HR: 0.42, 95% CI: 0.20-0.88, P = .02) than in the reference Maintenance Dialysis group. No difference in mortality risk between the Access Failure and reference group was found. Limitations: Single-center study. Possible residual confounding owing to the observational study design. Conclusions: Patients requiring acute or unplanned hemodialysis experience high mortality, and the nature of clinical presentation does influence outcomes. Most notable is the greater early mortality experienced by patients with AKI compared to other patient groups. Prospective definition of the nature of unplanned dialysis initiation is important to accurately measure and improve outcomes in this high-risk patient population. Human Research Ethics Committee Approval Number: CH62/6/2017-042.